3D Geological Model For Khasib, Tanuma, and Sa’di formations of Halfaya Oil Field in Missan Governorate-Southern Iraq - Fayadh, Arjwan Hamid; Nasser, Mad’hat E. (Iraqi Journal of Science, 2018)
A geological model is a spatial representation of the distribution of sediments and rocks in the subsurface. Where this study on Halfaya oil field; it is located in Missan governorate, 35 km southeast of the city of Amara. It is one of the main fields in Iraq because it is production high oil. This model contains the structure, and petrophysical properties (porosity, water saturation) in three directions. To build 3D geological models of petroleum reservoirs. Khasib, Tanuma, and Sa’di formations in Halfaya oil field have been divided into many layers depending on petrophysical properties and facies.